Une double discordance cardiaque complexe décompensée, à propos d’un cas et revue de la littérature - Nabila Soufi Taleb Bendiab; Rachid Djaziri; Fouad Sekkal; Nesrine Khedim; Abderrahim Meziane-Tani (Journal de la Faculté de Médecine d'Oran)
Abstract Double discordance is an extremely rare complex congenital heart disease; It is characterized by atrioventricular discordance followed by another ventriculo-arterial discordance. Its diagnosis is usually made in adulthood by imaging examinations. Its prognosis depends mainly on other associated congenital heart defects, arrhythmias and disorders of the conduction, as well as systolic function of the right ventricle in the systemic position. We report the case of a 23-year-old patient with a complex cyanogen heart disease. It is a double discordance associated to an interventricular communication with reverse shunt and an hypoplasia of the pulmonary artery.This Diagnosis was confirmed in multimodal imaging. Non-operated, the patient saw his functional status worsen rapidly with dyspnea which went from stage I to stage III-IV of the New York Heart Association (NYHA), and appearance of hypoxic and congestive signs. Through this observation, we have clarified the anatomoclinical characteristics of this complex congenital cyanogens heart disease, the necessary explorations and the different therapeutic options, as well as the pejorative role of its association with other congenital malformations.